2021
DOI: 10.1242/dmm.048249
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β3 deficiency promotes defective lipid metabolism and fibrosis in murine kidney

Abstract: Glomerulosclerosis and tubulointerstitial fibrosis are pathological features of chronic kidney disease. Transforming growth factor β (TGFβ) is a key player in the development of fibrosis. However, of the three known TGFβ isoforms, only TGFβ1 has an established role in fibrosis, and the pathophysiological relevance of TGFβ2 and TGFβ3 is unknown. Because Tgfβ3 deficiency in mice results in early postnatal lethality, we analyzed the kidney phenotype of heterozygous Tgfβ3-knockout mice (Tgfβ3+/-) and compared it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 71 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…A recent study reported that TGF-β3 may have antifibrotic and renoprotective properties; thus, it maintains renal homeostasis by inhibiting TGFβ1 activity. [30] However, Yu et al [31] reported that all TGF isoforms, including TGF-β3, have fibrogenic effects in renal cells, and the blockade of these isoforms will have a good therapeutic effect in reducing renal fibrosis. Another study noted that the expression level of TGF-β3 decreased in parallel with the improvement in kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that TGF-β3 may have antifibrotic and renoprotective properties; thus, it maintains renal homeostasis by inhibiting TGFβ1 activity. [30] However, Yu et al [31] reported that all TGF isoforms, including TGF-β3, have fibrogenic effects in renal cells, and the blockade of these isoforms will have a good therapeutic effect in reducing renal fibrosis. Another study noted that the expression level of TGF-β3 decreased in parallel with the improvement in kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, unlike other TGF isoforms (TGF‐β1 and TGF‐β2), information about TGF‐β3 is very limited and controversial. A recent study reported that TGF‐β3 may have antifibrotic and renoprotective properties; thus, it maintains renal homeostasis by inhibiting TGFβ1 activity [30] . However, Yu et al [31] .…”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, integrated bioinformatics methods assisted in an analysis of how key genes change in their expression to uncover potential DKD based on NGS dataset (GSE217709), and we identified total 958 DEGs, including 479 up regulated genes and 479 down regulated genes. [115], FGFR2 [116], ROR2 [117], RTN1 [118], NOTCH3 [119], JAK3 [120], IL18 [121], COL4A1 [122], CEBPD (CCAAT enhancer binding protein delta) [123], KIF26B [124], HES1 [125], CBS (cystathionine beta-synthase) [126], EGF (epidermal growth factor) [127], TRPM2 [128], HSPG2 [129], NOX4 [130], MYH9 [131], GLIS2 [132], TRPV4 [133], GSN (gelsolin) [134], DUSP2 [135], LRP5 [136], CD248 [137], GLI1 [138], PIM1 [139], TGFB3 [140], MDK (midkine) [141], TRPC6 [142], NKD2 [143], NUAK1 [144], CYS1 [145], POSTN (periostin) [146], STAT4 [147], AEBP1 [148] and NNMT (nicotinamide N-methyltransferase) [149] might be a possible genetic markers for susceptibility to renal fibrosis. MMP12 [150], BMP2 [151], IL33 [152], SORCS1 [153], IRF4 [154], PENK (proenkephalin) [77], mellitus.…”
Section: Discussionmentioning
confidence: 99%
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Elia Escasany is first author on ‘ Transforming growth factor β3 deficiency promotes defective lipid metabolism and fibrosis in murine kidney ’, published in DMM. Elia is a PhD student in the lab of Gema Medina-Gómez at Universidad Rey Juan Carlos, Madrid, Spain, investigating the role of TGFβ in renal fibrosis.…”
mentioning
confidence: 99%